Studi Eksplorasi Proses Perkuliahan Online dan Pengalaman Dosen Mengajar Pada Masa Pandemi Covid-19 di ITEKES Bali - Ni Nyoman Nuartini; LP Kartiningsih S.W; NLP Dina Susanti (Jayapangus Press, 2023)
At the beginning of the Covid-19 pandemic, Minister of Education and Culture of the Republic of Indonesia issued a Circular Letter of the Minister of Education and Culture No. 4 of 2020. This calls for all learning processes to be carried out. Study from home (online) as an effort to reduce contact and reduce the rate of transmission of Covid-19. This also applied at ITEKES Bali. This research aims to explore the experiences of ITEKES Bali lectures in carrying out the online lecture process during the Covid-19 pandemic. The design of this study is a qualitative with an exploratory approach. The respondents of this study were ITEKES Bali lecturers. All respondents provided informed consent and interviews were via video call. Data analysis was carried out by thematic analysis. The research results were presented in the form of themes. Most of the informants in this study stated that face-to-face learning is still more optimal than online learning. Informants realized that during a pandemic the choice of online learning was still the right choice and had to be implemented properly. This learning process provides a new experience for lecture and students both in terms of choosing models, media and teaching materials. Good internet access and creativity from all lectures are needed in developing learning methods. The lecture process at ITEKES Bali during the Covid 19 pandemic has been running quite smoothly, this needs to be maintained and continuously improved.